2019
DOI: 10.1016/j.radcr.2019.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Mammary analogue secretory carcinoma presenting as a cystic parotid mass

Abstract: We present a case of a 63-year-old male with an 8-year history of a left-sided cystic facial mass which recurred despite multiple drainage procedures. Imaging findings showed a cystic mass in the left parotid gland and it was surgically resected. Pathology confirmed it to represent a mammary analogue secretory carcinoma, a relatively newly described entity. This case illustrates that mammary analogue secretory carcinoma can masquerade as a cyst within the parotid gland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Out of a total of 226 studies published between 2010 and 2023, identified at initial search and screened for retrieval, 112 1–3,6–114 articles were included in the study, with a total of 674 patients described in these articles. The identification and screening process is described in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Out of a total of 226 studies published between 2010 and 2023, identified at initial search and screened for retrieval, 112 1–3,6–114 articles were included in the study, with a total of 674 patients described in these articles. The identification and screening process is described in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…14 Siderophages and blood in the background are common. Few cases of SC clinically present with a cystic mass, 4,18,19 and all of them occurred in the parotid gland. However, our case of lymph node SC, presenting as a lateral neck cystic mass, is quite unique from this point of view.…”
Section: F I G U R Ementioning
confidence: 99%